Pengembangan Model Surveilans Aktif Demam Berdarah Dengue Melalui Metode Pelaporan Kewaspadaan Dini Rumah Sakit (KDRS) di Kota Tasikmalaya - Aryo Ginanjar; Arda Dinata; Rohmansyah Wahyu Nurindra (ASPIRATOR - Journal of Vector-borne Disease Studies, 2016)
Dengue hemorrhagic fever (DHF) is still a health problem that difficult to handle in Indonesia including in Tasikmalaya City as one of DHF endemic city in West Java Province. However, the case reports from Hospital are usually delayed and incomplete. This research aims is to develop an active DHF surveillance model to increase the quality of Hospital’s early warning reports in Tasikmalaya City. This is a quantitative research using quasi experiment design and applies a design of pretest-intervention-posttest in a specific group. Qualitative approach is added to gain deeper information. Respondents of this research are 11 persons consist of 8 surveillance officers from 7 hospitals in Tasikmalaya City and 3 DHF program officers from Tasikmalaya City Heatlh Office. Interview and observation are conducted to measure knowledge and attitude of support facility’s officer also to measure the quality of hospital’s DHF early warning report. Intervention done as Workshop and Brief Training to determine which report model is most suitable to apply. Post-intervention monitoring was conducted in 3 months and all the research aspects are re-measured. The result shows that there are enhancements in all of the research aspects. The respondent’s knowledge level is increase from “less category” in pre-intervention to “enough-category” in post-intervention, attitude level is also increase from “enough category” to “well category”.The support facility are increasing as well from “less category” to “enough category” and the application of report system model is able to increase the quality of hospital’s early warning report from “less category” to “enough category”. The application of the Active Surveillance Model which developed by this research is able to increase the quality of Hospital’s early warning report, therefore if the model can be applied continuously, it expected to support more effective and efficient DHF handling effort in community.